Monitoring Barren-Ground Caribou Body Condition with Denésoliné Traditional Knowledge - Lyver, P.O.'B.; Dene First Nation, Lutsël K'é (ARCTIC, 2010)
Information from aboriginal elders and hunters on changes in barren-ground caribou (Rangifer tarandus) body condition can assist current management systems. Interviews with Denésoliné elders and hunters from Lutsël K’é, Northwest Territories, Canada, provided information on caribou body condition and environmental conditions. Hunters were accompanied in the field and asked to give a qualitative assessment of body condition for adult female caribou they harvested. Elders and hunters reported temporal and geographic variation in caribou body condition. Adult female caribou are selected in late winter (February to April) and bulls in fall (September) and spring (May) because they are fat. Hunters reported that adult female caribou were fatter during late winter in 2000 than in 2001. This difference was consistent with body condition impressions recorded in field surveys. Reports from hunters in interviews that adult female caribou were fatter in February than in March and April 2001 were also supported by hunters’ field impressions. Hunters identified areas where adult female caribou were in better condition than in other areas in 2000 and 2001. The number of caribou harvested and years of hunting experience influenced the distribution of hunters’ impressions of body condition. Interviews with hunters offer an inexpensive, repeatable approach to monitoring caribou body condition and range limitations, although ecological implications must be carefully interpreted. Des renseignements fournis par des aînés et des chasseurs autochtones sur les changements concernant l’état corporel du caribou des toundras (Rangifer tarandus) peuvent s’avérer utiles pour les systèmes actuels de gestion. Des entrevues menées auprès d’aînés et chasseurs Denésoliné de Lutsël K’é, dans les Territoires du Nord-Ouest au Canada, ont fourni des renseignements sur l’état corporel du caribou et sur les conditions environnementales. On a accompagné les chasseurs sur le terrain et on leur a demandé de faire une évaluation qualitative de l’état ...